A novel position and force coordination approach in four channel nonlinear teleoperation. (November 2016) - Mohammadi, Keyvan; Talebi, H.A.; Zareinejad, Mohammad
Abstract: In this paper, a novel control scheme is presented to achieve simultaneous position and force coordination in nonlinear teleoperation systems. Providing force feedback would facilitate the task for the operator and increase the performance. The four channel architecture is employed for this target as a high transparent structure. However, the stability issue has been a challenging problem, even in the sense of linear teleoperators. By employing a novel nonlinear damping, the stability of the closed loop system has been preserved even when the communication channel is subjected to time varying delay. In addition, no passivity condition is required for both the operator and the environment, a restrictive condition which is not always held in practice. We also proved through Lyapunov–Krasovskii functions that position and force tracking error will asymptotically converge to zero. The controllers do not require any knowledge of the robot dynamics except the gravity terms. In order to verify the effectiveness of the proposed controller, a simulation result is presented, illustrating both position and force coordination in such nonlinear systems.